Valorization of macroalgae through fermentation for aquafeed production: A review - Chun, Yao Ang; Annita Seok Kian Yong; Sujjat Al Azad; Leong, Seng Lim; Wahidatul Husna Zuldin; Mohammad Tamrin Mohamad Lal (Multidisciplinary Digital Publishing Institute, 2021)
The increased development of aquaculture has resulted in increased demand for highprotein aquafeed. An increased demand for high-protein aquafeed means an increase in exploitation of unsustainable protein sources such as fishmeal for aquafeed production. Thus, alternative protein sources such as fermented macroalgae is explored. Fermented macroalgae had been tested as aquaculture diets in some studies, but with limited coverage in relation to aquaculture. Therefore, this review provides a new perspective regarding their nutritional qualities as aquaculture diets, and their impacts on growth performances of aquaculture animals.